2019
DOI: 10.1002/rnc.4709
|View full text |Cite
|
Sign up to set email alerts
|

Distributed fusion cubature Kalman filters for nonlinear systems

Abstract: Summary This paper is concerned with the distributed fusion estimation problem for multisensor nonlinear systems. Based on the Kalman filtering framework and the spherical cubature rule, a general method for calculating the cross‐covariance matrices between any two local estimators is presented for multisensor nonlinear systems. In the linear unbiased minimum variance sense, based on the cross‐covariance matrices, a distributed fusion cubature Kalman filter weighted by matrices (MW‐CKF) is presented. The propo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Then,L N can be easily obtained by substituting (29) into (25). Furthermore, usingx k|Y N obtained in (21), the second layer of the TLNF filter is designed to enhance the robustness against unexpected measurement noise.…”
Section: Volume 8 2020mentioning
confidence: 99%
See 1 more Smart Citation
“…Then,L N can be easily obtained by substituting (29) into (25). Furthermore, usingx k|Y N obtained in (21), the second layer of the TLNF filter is designed to enhance the robustness against unexpected measurement noise.…”
Section: Volume 8 2020mentioning
confidence: 99%
“…Hao et al [28] proposed a weighted measurement fusion (WMF) algorithm that showed asymptotic optimality using the UKF for a nonlinear system with multiple sensors. Hao et al [29] proposed a distributed fusion CKF weighted by matrices (MW-CKF) based on the KF framework and spherical cubature rule for multisensory nonlinear systems. Sun et al [30] reviewed various distributed fusion estimation (DFE) algorithms for multisensor networked systems comparing performance.…”
Section: Introductionmentioning
confidence: 99%
“…The estimation performance is accumulated mean square error (AMSE) in position at time k [41]- [43]:…”
Section: Simulation Examplementioning
confidence: 99%
“…As for distributed state estimation problems, many researchers have made a great deal of work with abundant results. [7][8][9][10][11][12] Just name a few for examples. A consensus-based distributed algorithm, which executed some consensus steps about measurements and innovation covariances, was proposed to approximate the centralized Kalman filter.…”
Section: Introductionmentioning
confidence: 99%